TRATAMIENTO Y PRESENCIA DE LAS MUJERES EN LA PRENSA. GÉNERO, LENGUAJE Y COMUNICACIÓN - Simelio Solà, Núria (2019)
This article presents the outcomes of a content analysis study about the representation of women in the Spanish Press, which is a part of a larger research focusing on the Spanish Press between 1974-2000. Our research provides a novel contribution to other research in this area by analyzing in a comparative, systematic and longitudinal way representations of social and political relationships communicated by the press. We examine how quite often, journalists in the media use references to the different type of actors as a stylistic device for pushing their arguments. For the most part, these rhetorical devices go unnoticed but often take the form of generalizing statements and use preconceived ideas and prejudices. Our results demonstrate that the actors who the media devoted less time to during the studied periods also were the actors that received worse treatment. Specifically, women actors receive a minor attention among the newspapers. Also, women appeared as a passive agent, never were focused on as a public representative and they were relegated to the private sphere. Principally, women were focused on while doing sports, cultural and entertainment activities or when they were victims, whereas a minority of them was shown doing political activities. Finally, we elaborate patterns of style, language and news production in order to promote a positive media view of an egalitarian society.